DIFFERENTIATION OF FOCAL NODULAR HYPERPLASIA FROM HEPATOCELLULAR CARCINOMA IN THE NONCIRRHOTIC LIVER WITH A CT-BASED RADIOMICS NOMOGRAM (World Bulletin of Public Health, 2023)
The main purpose of our study was to develop and validate a radiomics for differentiating focal nodular hyperplasia (FNH) from hepatocellular carcinoma (HCC) in the non-cirrhotic liver before the surgery
Keywords: Focal nodular hyperplasia; Hepatocellular carcinoma; Computer tomography; X-ray